Assessment of Sound Pollution in Butwal Sub-Metropolitan City, Rupandehi, Nepal - Sapkota, Babin Sharma (Devkota Journal of Interdisciplinary Studies, 2023)
Sound pollution in recent times has been considered as one of the significant problems that impact the quality of life worldwide. This paper analyzes the sound level in different locations in Butwal sub-metropolitan city. The traffic sound level in Butwal was observed at 16 major chowks of Butwal city three times in a day i.e morning, day and evening time, in all the monitoring stations. The sound level was measured in the morning at 7 to 9 am, in the afternoon at 1 to 3 pm and in the evening at 5 to 7 pm. The instrument was operated for 5 minutes at each monitoring station. From the observation, the highest level of sound was observed in Bus Park & Puspalal Park and Basecamp i.e. 83 dB, the second highest was observed in Golpark Bhudkichowk i.e. 82 dB, and the third highest was recorded from finance chock old Buspark Palpa Buspark i.e. 85 dB. Similarly the lower level of noise among the monitoring stations was recorded at Hatbazar area i.e. 76 dB, the sound level of Yogakoti, Chauraha, Hatbazar was observed less than 80 dB and it was observed more than 80 dB at Finamne chowk, Buspark, Puspalal park, Palpa Buspark, Golpark, Kalika chowk, Basecamp, Milonchowk, Bhudkichowk, Old Buspark, Traffic Chowk, Laxminagar chowk and Durga mandir chowk. From the observation it was found that the noise level of most of the places in Butwal sub-metropolitan city was high especially in daytime.